IL-17A-driven psoriasis is critically dependent on IL-36 signaling - Fischer, Berenice; Kübelbeck, Tanja; Kolb, Antonia; Ringen, Julia; Waisman, Ari; Wittmann, Miriam; Karbach, Susanne; Kölsch, Stephan Marcus; Kramer, Daniela (Frontiers in Immunology, 2023)
Plaque psoriasis is an autoinflammatory and autoimmune skin disease, affecting 1-3% of the population worldwide. Previously, high levels of IL-36 family cytokines were found in psoriatic skin lesions, thereby contributing to keratinocyte hyperproliferation and infiltration of immune cells such as neutrophils. While treatment with anti-IL36 receptor (IL36R) antibodies was recently approved for generalized pustular psoriasis (GPP), it remains unclear, if targeting the IL36R might also inhibit plaque psoriasis. Here we show that antibody-mediated inhibition of IL36R is sufficient to suppress imiquimod-induced psoriasis-like skin inflammation and represses the disease's development in a model that depends on IL-17A overexpression in the skin. Importantly, treatment with anti-IL36R antibodies inhibited skin inflammation and attenuated psoriasis-associated, systemic inflammation. This is possibly due to a widespread effect of IL36R inhibition, which not only suppresses pro-inflammatory gene expression in keratinocytes, but also the activation of other immune cells such as T-cells or dendritic cells. In conclusion, we propose that inhibition of the IL-36 signaling pathway might constitute an attractive, alternative approach for treating IL-17A-driven psoriasis and psoriasis-linked comorbidities.